Educational and methodological manual for conducting laboratory classes on special epizootology on infectious diseases of ruminants and pigs : еducational and methodological manual - Kisera, Ya.; Martyniv, Yu.; Matviishyn, T. (Stepan Gzhytskyi National University of Veterinary Medicine and Biotechnologies, 2024)
The manual covers material on 39 infectious diseases, including: 12 infectious diseases of cattle (leukemia, emphysematous carbuncle, paratuberculosis, campylobacteriosis, contagious pleuropneumonia, plague, malignant catarrhal fever, infectious rhinotracheitis, parainfluenza, viral diarrhea, spongiform encephalopathy, nodular dermatitis) , 11 infectious diseases of small cattle (bradzot, infectious enterotoxemia, infectious agalactia, infectious catarrhal fever, hoof rot, contagious pustular dermatitis, infectious epididymitis, smallpox, visna-maedi, scrapie, malignant edema), 16 infectious diseases of pigs (classic and African swine fever, erysipelas, reproductive and respiratory syndrome, influenza, infectious atrophic rhinitis, vesicular disease, vesicular exanthema, enzootic encephalomyelitis, transmissible gastroenteritis of pigs, colienterotoxemia, dysentery, enzootic pneumonia, hemophilic polyserositis, hemophilic pleuropneumonia of pigs, chlamydia). Issues of diagnosis, treatment, immunoprophylaxis, general prevention and control measures are highlighted.
Keywords: epizootology; infectious diseases of ruminants; infectious diseases of pigs